DESIGNING GEOGRAPHIC INFORMATION SYSTEM CULINARY TOUR LOCATION IN THE WEST LOMBOK REGION MOBILE-BASED APPLICATION - Erniwati, Surni; Subki, Ahmad (Jurnal Pilar Nusa Mandiri, 2020)
Lombok Island is an island in West Nusa Tenggara which is separated by the Lombok and Bali straits to the west and Alas Strait to the east of Sumbawa. The tourism potential in the West Lombok region is currently in great demand by local and foreign tourists because the tourist objects offered in the West Lombok region are very diverse, such as natural, religious, cultural, and culinary tours. Many restaurants offer culinary but often when indicating the location of a culinary, the information obtained is sometimes limited to street names and location characteristics. Meanwhile, the clarity of where the culinary location is not mapped in detail. So far, culinary connoisseurs use manual methods to find culinary locations such as Instagram, Facebook, and Blogspot. For tourists, this manual method is less effective because it consumes a lot of time and address information for getting to culinary locations is inadequate. One solution that can be used to obtain information is a geographic information system (GIS). The goal is to make it easier for culinary lovers to find culinary tourism locations. The research method used in this research is the Research and Development research method with preliminary stages, data and information collection, interviews and observations, system design with modeling, design validation, design revision, development, limited trial, limited trial revision, trial field, revision of field trials, dissemination, and implementation.